On the identity of Hyla strigilata Spix, 1824 (Anura : Hylidae): redescription and neotype designation for a ghost taxon - Pimenta, Bruno V. S.; Faivovich, Julian [UNESP]; Pombal Júnior, José P. (Magnolia Press, 2007)
Recent field work in Atlantic Rain Forest patches in the southern region of the State of Bahia, Brazil, resulted in the discovery of some populations of an unidentified species of the Scinax catharinae group. An extensive literature review, along with the examination of specimens and distribution patterns of all known species of this group, showed that Hyla strigilata Spix, 1824, a long confused species with lost type material, is an available name for the specimens from Bahia. In order to clarify the taxonomic problems surrounding this taxon, the nomenclatural history of Hyla strigilata is reviewed and a neotype is designated, described, and figured. The association of this name to extant populations from southern Bahia and its consequent stabilization is considered important since it is the type species of the genus Ololygon, a name available for the clade of Scinax catharinae. Data on habits, habitat, and geographic distribution are also presented.
Keywords: Scinax strigilatus; Scinax catharinae species group; Ololygon; Scinax catharinae clade; Dendropsophini